2018
DOI: 10.1371/journal.ppat.1006914
|View full text |Cite
|
Sign up to set email alerts
|

Lung macrophage scavenger receptor SR-A6 (MARCO) is an adenovirus type-specific virus entry receptor

Abstract: Macrophages are a diverse group of phagocytic cells acting in host protection against stress, injury, and pathogens. Here, we show that the scavenger receptor SR-A6 is an entry receptor for human adenoviruses in murine alveolar macrophage-like MPI cells, and important for production of type I interferon. Scavenger receptors contribute to the clearance of endogenous proteins, lipoproteins and pathogens. Knockout of SR-A6 in MPI cells, anti-SR-A6 antibody or the soluble extracellular SR-A6 domain reduced adenovi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
67
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(68 citation statements)
references
References 99 publications
1
67
0
Order By: Relevance
“…Analysis of mouse spleen sections at 30 min after intravenous administration of HAdv-C5 and staining with antibodies specific for the virus and defined macrophage markers revealed that shortly after intravenous delivery, HAdv particles predominantly accumulate in two distinct populations of macrophages in the splenic marginal zone, with one population expressing CD169 (MOMA-2) and the other macrophage scavenger receptor MARCO (SR-A6 [38]). It has also been shown that deletion of the hexon HVR1 loop in HAdv-C5 was sufficient to abrogate virus binding and transduction of alveolar macrophages and that MARCO can mediate entry into macrophages for Ad of species B and D (HAdv-B35 and HAdv-D26, respectively) [53]. However, it appears that when HAdv interaction with hepatic cells is reduced via pharmacological conditioning or through ablation of interactions with blood factors by introducing mutations to the virus capsid [12,51], the accumulation of HAdv in the spleen is significantly increased [51].…”
Section: Mechanisms Of Hadv Sequestration In Tissue Macrophagesmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of mouse spleen sections at 30 min after intravenous administration of HAdv-C5 and staining with antibodies specific for the virus and defined macrophage markers revealed that shortly after intravenous delivery, HAdv particles predominantly accumulate in two distinct populations of macrophages in the splenic marginal zone, with one population expressing CD169 (MOMA-2) and the other macrophage scavenger receptor MARCO (SR-A6 [38]). It has also been shown that deletion of the hexon HVR1 loop in HAdv-C5 was sufficient to abrogate virus binding and transduction of alveolar macrophages and that MARCO can mediate entry into macrophages for Ad of species B and D (HAdv-B35 and HAdv-D26, respectively) [53]. However, it appears that when HAdv interaction with hepatic cells is reduced via pharmacological conditioning or through ablation of interactions with blood factors by introducing mutations to the virus capsid [12,51], the accumulation of HAdv in the spleen is significantly increased [51].…”
Section: Mechanisms Of Hadv Sequestration In Tissue Macrophagesmentioning
confidence: 99%
“…Recent studies by Maler et al [52] demonstrated that mouse alveolar macrophages are readily transduced in vitro by HAdv-C5 via interaction with MARCO. It has also been shown that deletion of the hexon HVR1 loop in HAdv-C5 was sufficient to abrogate virus binding and transduction of alveolar macrophages and that MARCO can mediate entry into macrophages for Ad of species B and D (HAdv-B35 and HAdv-D26, respectively) [53]. Therefore, in the context of intravenous administration of high doses of coagulation FX-binding-ablated viruses, upon passing through the splenic marginal zone, the virus particles can directly bind to scavenger receptor MARCO on the surface of macrophages.…”
Section: Mechanisms Of Hadv Sequestration In Tissue Macrophagesmentioning
confidence: 99%
“…In the same study, the combination of an anti-CD46 antibody and cyclic-RGD peptides on patient myeloma cells mediated complete protection against killing by HAdV26, suggesting that both receptors, CD46 and ␣v integrins, are utilized by the virus to infect these target cells (27). Finally, very recently, the scavenger receptor SR-A6 has been implicated in facilitating HAdV26 entry into murine alveolar-macrophage-like MPI cells (28). HAdV26 receptor usage has also been investigated for peripheral blood mononuclear cells (25) or malignant B cells (27), while HAdV26 receptor usage in epithelial cells is less well defined.…”
mentioning
confidence: 91%
“…Studies with AdV show further cell-to-cell heterogeneity, namely in virion binding to the cells [20], endosomal and cytoplasmic trafficking [21,22], and virion uncoating [23 -28]. Single-cell, single-particle analyses show that different steps of entry occur 5 with different efficiencies in individual infected cells and thus the number of vDNAs delivered into the nucleus varies between cells [21,25,27].…”
Section: Introductionmentioning
confidence: 99%